Corporation and Corporate Solidarity: Traditions, Approaches, Russian Reality - Евгения Алексеевна Коршунова (Journal of Economic Sociology, 2010)
The paper provides the historical and sociological analysis of the term “corporation”: its origin and the main traditions of its use are in the focus (the tradition which stems from Durkheim and “economics” tradition in Europe and Japan). The author makes an attempt to produce empirical study of corporate solidarity in the context of modern Russia (case study of a plan in Nijniy Novgorod). It was shown that the current Russian corporation combines these two traditions inside. Individuals imagine the corporation as integral overindividual and referent group, the members of which they are at the same time.